The Influence of Work Life Balance, Career Development and Compensation on Employee Performance at PT Busana Teen Agrakreati Bantul Yogyakarta - Pranesti, Oktofi Wahyu; Gunawan, Hamzah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
In today's competitive industrial world, qualified human resources are crucial for companies to achieve their goals. One way to achieve this is by understanding employee performance within the company. This study aims to analyze the influence of work-life balance, career development, and compensation on employee performance. The sample in this study consisted of 100 respondents who are employees of PT Busanaremaja Agracipta, Bantul, Yogyakarta. The data collection technique used was a survey method with the research instrument in this study being a questionnaire. The results of the instrument test stated that the data in this study was distributed abnormally, so it was necessary to change the data into Natural Logarithm (LN) form. Then, from the transformed data, a regression model was produced that was free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Work-life balance does not have a significant effect on employee performance, (2) Career development has a significant effect on employee performance, (3) Compensation has a significant effect on employee performance, (4) Work-life balance, career development and compensation have a simultaneous effect on employee performance. These results have implications for further researchers to examine work-life balance in relation to its relationship with employee performance in order to influence employee performance.